2002
DOI: 10.1055/s-2002-33602
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effects of LH on Release of Melatonin and Activities of its Synthesizing Enzymes NAT and HIOMT in Organ-Cultured Pineal Glands of Female Rats

Abstract: The pineal hormone melatonin (N-acetyl-5-methoxytryptamine) exerts antigonadotropic effects in some mammalian species. To evaluate the effect of luteinizing hormone (LH) on melatonin release and its synthesizing enzyme activities in pineal glands, pineals of adult female rats undergoing diestrus were organ-cultured in a medium containing 10(-12), 10(-10) or 10(-8) M LH for 6 h. Melatonin release increased significantly in pineals cultured with 10(-12) and 10(-10) M LH, as compared to control values. Similarly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Similar changes in the estrous cycle have been reported in HIOMT activity [18] and AANAT activity [22]. We showed that LH at relatively low physiological levels stimulates melatonin secretion from the female pineal gland, whereas high LH levels, which are about equivalent to those in the circulating plasma during the preovulatory LH surge, have no effect [16]. Thus, LH may affect pineal melatonin secretion, particularly the nocturnal secretion, under physiological conditions.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar changes in the estrous cycle have been reported in HIOMT activity [18] and AANAT activity [22]. We showed that LH at relatively low physiological levels stimulates melatonin secretion from the female pineal gland, whereas high LH levels, which are about equivalent to those in the circulating plasma during the preovulatory LH surge, have no effect [16]. Thus, LH may affect pineal melatonin secretion, particularly the nocturnal secretion, under physiological conditions.…”
Section: Introductionsupporting
confidence: 84%
“…Previous studies have reported that luteinizing hormone (LH) increases melatonin content and release in organ‐cultured pineal glands from adult male rats [13, 14]. We further showed that LH at relatively low physiological levels, which are equivalent to levels in the plasma at diestrus, stimulates melatonin secretion, mainly by increasing AANAT activity, in organ‐cultured pineal glands from adult female rats [16]. These studies suggest that pineal melatonin‐synthesizing cells, namely pinealocytes, are direct targets for LH.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Finally, it has been proposed that some pineal cells synthesize LHRH or a LHRH-like peptide (Pévet et al, 1980b). Until now, few studies have reported an effect of this peptide on pineal metabolism: it is proposed to stimulate HIOMT activity (Cardinali et al, 1976;Cardinali and Vacas, 1979), regulate the formation of granular vesicles and the process of protein and/or peptide secretion (Haldar-Misra and Pévet, 1983), and increase MEL secretion, although only moderately (Mess et al, 1991), mainly via an activation of AA-NAT (Hosaka et al, 2002). Seasonal variations of LHRH have been observed in the pineal gland of the rat (with a maximum in March/ Joseph, 1976) and sheep (King and Millar, 1981).…”
Section: Multiple Regulation Of Pineal Melatonin Synthesis In Mammalsmentioning
confidence: 99%
“…Melatonin is produced from l ‐tryptophan, through a four step reaction, controlled by specific enzymes, one of them is N‐acetyl‐serotonin transferase (NAT) [16]. Gene expression for this enzyme has been found in numerous tissues including brain, retina, and digestive system [17].…”
Section: Introductionmentioning
confidence: 99%